Yield and crown structure characteristics in a red oak (Quercus rubra L.) stand: Case study - Szabó, Fruzsina; Ábri, Tamás; Rédei, Károly (Acta Agraria Debreceniensis, 2021)
The paper provides the results of a detailed analysis of timber volume and several important crown variables of red oak (Quercus rubra L.) based on an experimental plot in eastern Hungary. At the age 32 years the crop trees belonged to different height classes. If the volume of the mean tree from height class I was considered as 100%, the volume of the mean tree of class II was 59%, and the mean tree of class III was only 36%. It appeared that there was a significant correlation between crown indices and yield. For this reason, diameter at breast height showed a positive linear correlation with crown diameter (R2= 0.6211). Additionally, there was also positive linear relationship between crown diameter and volume (R2= 0.6908). The variation of crown indices is height even within the same stand and indicates the importance of following a selective thinning operation method.